Efficient photoreduction of hexavalent uranium over defective ZnO nanoparticles by oxygen defect engineering. Issue 37 (1st September 2022) - Deng, Xiaochuan; Zou, Geng; Tu, Boyuan; Hu, Mingfang; Zhu, Wenkun; He, Rong; Chen, Tao
Abstract : The oxygen-defect engineering of ZnO-400 nanosheets to enhance their photocatalytic performance for U(vi ) reduction. Abstract : Photoreduction of soluble hexavalent uranium to insoluble tetravalent uranium U(iv ) is a promising strategy to achieve effective uranium extraction from radioactive wastewater. Herein, ZnO nanoparticles (ZnO NPs) with an abundance of oxygen vacancies (Ov ) were prepared to achieve U(vi ) photoreduction under simulated sunlight irradiation. The analysis of the band structure revealed that the introduction of Ov into ZnO NPs both effectively broadened the response range to visible light and narrowed the band gap. ZnO-400 displayed the maximum removal rate which reached 98.5% with an apparent rate value of 0.019 h −1 in 200 mg L −1 of U(vi ) solution. Accordingly, the introduction of Ov into ZnO NPs tailored the energy level structure and enhanced the spatial separation efficiency of electron–hole pairs, thereby further realizing the improvement of U(vi ) extraction efficiency for ZnO-400. This work provided a promising strategy for designing advanced photocatalysts by the vacancy engineering of metal oxides for selective U(vi ) extraction.